Strategi Medical Tourism Thailand Dalam Mewujudkan Branding Negaranya Sebagai “Thailand As A World Class Health Care Provider” Pada Tahun 2014-2018 Di Dunia Internasional - Wedana, Gede Nanda Surya; Priadarsini, Ni Wayan Rainy; Parameswari, A.A.A Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
Thailand is one of the countries with great potential in the medical tourism sector. From 2003 to 2008 the Thai government had a program to increase its medical tourism entitled “Thailand: The Excellent Medical Hub of Asia”. From 2008 to 2014 the Thai government did not include medical tourism on its government agenda, where in 2014 there was a decline in the arrival of foreign patients. The Thai government seeks to maximize the sector by creating branding for its country as “Thailand As A World Class Health Care Provider” from 2014 to 2018. To realize the country's branding, the Thai government implemented a branding strategy, namely the promotion of Thai medical tourism through the application of minimum prices, the Thai government's visa policy, and the development of Thai medical facilities and services.  Keywords : medical tourism, nation branding, strategy, Thailand